Pengaruh Kepemilikan Manajerial, Kepemilikan Institusional, Kepemilikan Asing dan Kepemilikan Keluarga Terhadap Manajemen Pajak pada Perusahaan Munufaktur yang Terdaftar di Bursa Efek Indonesi Periode 2019-2023 - Arif Nurman Hakim; Sundjoto; Sri Rahayu; Sofyan Lazuardi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Tax implementation in Indonesia is not balanced and there are still many tax problems that occur in Indonesia. From 2023 data, there are 0.79 percent of tax dispute cases, which means that taxpayers are still carrying out tax planning practices that can harm state revenues. This research aims to test whether managerial ownership, institutional ownership, foreign ownership and family ownership have an effect on tax management. To answer this question, this research uses agency theory where there is a conflict of interest between the agent and the principal. The population of this research is all manufacturing companies listed on the Indonesia Stock Exchange from 2019 to 2023. The sample uses purposive sampling with the main criteria being those that have tax disputes in the tax court. This research analysis tool uses multiple linear regression. The research results state that management ownership and foreign ownership have no effect on tax management, while institutional ownership has a negative effect on tax management and family ownership has an effect on tax management. The implications of the results of this research indicate the need for supervision of companies that have family ownership.